2021
DOI: 10.1002/chem.202100936
|View full text |Cite
|
Sign up to set email alerts
|

Heptacene: Synthesis and Its Hole‐Transfer Property in Stable Thin Films

Abstract: Heptacene (1) has been produced via a monoketone precursor, 2, which was prepared from 1,2,4,5tetrabromobenzene in nine steps in a total yield of 10 %. Compound 2 was converted to 1 quantitatively by heating at 202°C. Heptacene exhibited high thermal stability in the solid state without any observable change over two months. To investigate the potential value of 1 as a material for p-type organic field-effect transistors (OFETs), top-contact OFET devices were fabricated by vacuum deposition of 1 onto a hexamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 77 publications
0
15
0
2
Order By: Relevance
“…3 ). This important result is comforted by the observation that bulk heptacene 31 or even thin films of heptacene 32 are also stable for months at RT when stored in a nitrogen-filled glove-box.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 ). This important result is comforted by the observation that bulk heptacene 31 or even thin films of heptacene 32 are also stable for months at RT when stored in a nitrogen-filled glove-box.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, we have also obtained heptacene and benzohexacene by cheletropic decarbonylation at moderate temperature, confirming the thermal stability of these higher acenes 31 . And lately, Miyazaki et al prepared stable thin films of heptacene 32 . The preparation of even longer acenes in bulk form has been indeed an attracting challenge since Clar’s prediction in 1964 claiming that the synthesis of octacene (and beyond) was a remote target 33 .…”
Section: Introductionmentioning
confidence: 99%
“… 41 However a significantly high μ FE of 2.2 cm 2 V −1 s −1 was recently published for heptacene grown layers exhibiting very small crystals with an estimated size of 17 nm. 20 In order to achieve a better understanding of hole transport (with increasing n ) in new n -acene molecules a thorough study of field effect mobility extraction is thus necessary. In the next section, we analyse the behaviour of μ FE according to various parameters such as device geometry and operation mode.…”
Section: Resultsmentioning
confidence: 99%
“…First attempts to integrate heptacene (generated from monocarbonyl precursor) in OTFTs were reported very recently by T. Miyazaki et al and showed promising μ FE values. 20 This powerful concept of having a stable and soluble proactive precursor, which can be transformed into acene on demand in quantitative yield and very high-quality, paves the way not only to the integration of promising novel molecules in organic devices, but it also allows for deepening more fundamental questions such as chemical topology, heteroatom doping, substitution or effect of open-shell configuration on OTFT performance. Furthermore, it will shed light on the validity of the above-mentioned law of charge mobility evolution with increasing n .…”
Section: Introductionmentioning
confidence: 99%
“… 7 Therefore, larger acenes beyond pentacene ( 5A ) are promising candidates for applications in optoelectronic devices. 8 , 9 Due to their pronounced instability toward light and oxygen, large acenes are difficult to handle under normal conditions. 10 Despite this, the formation of comparably stable, ordered film structures was recently reported for hexacene ( 6A ) and heptacene ( 7A ).…”
Section: Introductionmentioning
confidence: 99%